HUBUNGAN POLA ASUH ORANG TUA DENGAN PRESTASI BELAJAR SISWA DALAM MATA PELAJARAN PENJAS PADA SISWA KELAS X SMA NEGERI 1 PUJUT TAHUN PELAJARAN 2016/2017 - Wegu, Harianto; Satrianingsih, Baiq; Lubis, M. Ridwan (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2017)
The problem in this research was the lack of parental concern in nurturing, guiding, caring and educating their children in a family environment. The iimplementation of good parenting parents were parenting authoritarian, democratic or permissive that can greatly affect the learning achievement of children in school.The learning achievement of the X grade students SMAN I PujutÂ  was low, however they have raeched the KKM. It can be seen from many students who take the remedial in order to improve their achievemnet for the KKM. Here, the parents role in taking after their child were expected to influence the students learning achievement in school. The purpose of this study was to determine whether there was any correlation of parenting toward student achievement in sports and physical education subject at the X grade students SMAN I Pujut. In this study, the population was allX grade students of SMAN I Pujut thatconsisted of four classes i.e. X MIA1, MIA2, SS1 and SS2, with the number of students = 90 students. The sample used X SS2 that was selected randomly ( 25 students ). The sampling technique in this study was cluster random sampling. The data collection method used questionnaire method and documentation as the mandatorymethod while the interview and observation as a supporting method. The data analysis used statistical formula that is the product moment correlation. The results of the analysis showed that r-score = 0.769 and r-table= 0.396 at significance level of 5% with N = 25. It meant that r-score was higher than r-table (0.769> 0.396). It can be concluded that H0 is rejected and Ha is accepted, it said that there was a significant correlation of parenting toward student achievement in sports and physical education subject at the X grade students SMAN I Pujut